103k views
1 vote
Let a, b, c and x elements in the group G. In each of the following solve for x in terms of a, b, and c.

Solve axb =c

User Luis Orduz
by
4.6k points

1 Answer

3 votes

Answer:


x=c.a^(-1).b^(-1)

Explanation:

Given equation,


axb = c-----(1)


(axb) ( a^(-1).b^(-1) ) = c.(a^(-1)b{-1})


(xb)(a)(a^(-1).b^(-1) ) = c.(a^(-1)b{-1}) ( commutative law of multiplication )


(xb)(a.a^(-1)).b^(-1) = c.a^(-1)b{-1} ( Associative property )


(xb).e.b^(-1) = c.a^(-1)b{-1}


(xb).b^(-1)=c.a^(-1).b^(-1) ( identity property )


x.(b.b^(-1))=c.a^(-1).b^(-1) ( Associative property )


x.e=c.a^(-1).b^(-1)


x=c.a^(-1).b^(-1) ( identity property )

User Vegidio
by
4.5k points